Social transformation among Sahrāwī desert nomads: the hidden logic of Ḥassānīya socio-geographical networks - Isidoros, K (2014)
Scholarship on the Western Sahara conflict has long puzzled over an ‘extraordinary leap’ of Sahrāwī tribes to the status of refugees and citizens of an exiled nation-state. It has glossed over this process as a modernising and civilising act of detribalisation, applauded women’s recent political appearance within a sovereignty-solidarity discourse, yet simultaneously used an insecurity discourse to measure Sahrāwī ‘performance’ hypercritically from inside the nascent state’s corridors. This ethnographic study observes Sahrāwī political action differently, by looking out from inside the tent and through the eyes of women.The thesis re-examines Sahrāwī tribe to state transition using a new framework of women’s tents and circulating, veiled males. Drawing on two years of anthropological fieldwork, the significance of the tent emerges as the decision-making centre for both men and women whereby the domestic is the political. I argue that women must be analytically recognised as political architects, utilising and presiding over tents as a female political economy of affection that casts a centralised political constellation across the Sahara. Not only do these fresh insights of Sahrāwī strategic tribe-state symbiosis and tactical nomadic sedentarisation overturn received anthropological wisdom on the stele of ‘tribe’, but it is women and their tents that can offer explanations for the ‘leap’ from genealogical reckoning to nationalist consciousness. This study presents comparative ethnography to engage critically with anthropology’s ‘great debates’ and popularised tropes regarding veiling, patriarchy, gendered space and power, and ‘tribal’ society. A different analytical light is cast on the gendered use of the exoticised Middle Eastern ḥarīm and of new hybrid forms of human socio-political reorganisation that challenge Western default notions of nation and state to suggest the need to rethink ‘tribe’.